DIGITAL COMPETENCE IN FOREIGN LANGUAGE TEACHING - Abdanbekova Nilufar Rixsiyevna (Modern American Journals, 2025)
This article investigates the crucial role of digital technology competence in foreign language teaching amidst the increasing adoption of blended and online education models. The study proposes a pedagogical framework aimed at enhancing digital skills among pre-service and in-service language teachers. Empirical evidence from qualitative and quantitative data supports the framework’s effectiveness in improving teaching practices and learner engagement.
Keywords: Digital competence¹, foreign language teaching, blended learning², educational technology, teacher professional development, online pedagogy